PERAN GURU DAN LITERASI BUDAYA DALAM PEMBENTUKAN TOLERANSI SISWA SEKOLAH DASAR - Rita Ratna Sari; Haifaturrahmah Haifaturrahmah; Sukron Fujiaturrahman (Jurnal Al-Fatih, 2025)
This study aims to analyze the role of teachers and cultural literacy in the formation of tolerance attitudes among elementary school students using a qualitative method with a Literature Review approach. The literature used was obtained from reputable databases such as Scopus, DOAJ, and Google Scholar with a publication range from 2020 to 2025. The findings show that teachers play a key role as role models and facilitators in instilling human values through reflective, empathetic, and collaborative learning. Cultural literacy contributes to increasing empathy, social awareness, and respect for diversity among students. The integration of both creates a harmonious and inclusive school climate, supporting the formation of strong social character. However, most of the research remains descriptive and has not examined causal relationships or the long-term impact of cultural literacy implementation. Therefore, further research is needed to develop an integrated digital cultural literacy model and the role of teachers as a contextual learning strategy that adapts to the Merdeka Curriculum, in order to strengthen humanistic and sustainable character education.